Influence of Perceived Usefulness, Ease of Use, User Satisfaction, and Security Against Intentional Behavior Using GoPay E-Wallet - Aini, Nur; Parinduri, Annisya Fitri Khairina (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2024)
This research aims to analyze the population of Batam City, especially application-based GoPay e-wallet users from Gen Z and Millennials (20-30 years). This research was also conducted to complement research on behavioral intentions when using the GoPay e-wallet by developing replication of previous research. This research uses perceived usefulness, perceived ease of use, perceived user satisfaction, and perceived security as independent variables and behavioral intention as the dependent variable. The population of this study consisted of residents of the city of Batam and used a purposive sampling technique so that the sample consisted of 100 respondents. The data analysis technique used is quantitative descriptive analysis. The data described was processed using SmartPLS 3.29 software. The research results show that perceived usefulness, ease of use, and user satisfaction influence behavioral intentions when using the GoPay e-wallet. However, perceived security does not influence behavioral intentions when using the GoPay e-wallet.